Data Quality Measures and Data Cleansing for Research Information Systems- - Otmane Azeroual; Gunter Saake; Mohammad Abuosba (Journal of Digital Information Management, 2018)
The collection, transfer and integration of research information into different research information systems can result in different data errors that can have a variety of negative effects on data quality. In order to detect errors at an early stage and treat them efficiently, it is necessary to determine the clean-up measures and the new techniques of data cleansing for quality improvement in research institutions. Thereby an adequate and reliable basis for decision-making using an RIS is provided, and confidence in a given dataset increased.

Data Quality Measures and Data Cleansing for Research Information Systems - Otmane Azeroual; Gunter Saake; Mohammad Abuosba (Journal of Digital Information Management, 2018)